Impact of arbovirus events on selected hospital indicators, Cienfuegos, Pediatric Hospital (2014-2018) - Delfin Rodríguez Buergo; Hilda María Delgado Acosta; Maira de los Ángeles Valladares Vílchez; Nestor Miguel Rojas Fernández; Alexis Díaz Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Introduction: Arboviruses have emerged as a public health problem. Objective: To identify modifications in hospital indicators in relation to the occurrence of arbovirus events in the province. Method: hospital indicators selected in the 2014-2018 period: occupational index, hospital stay, turnover rate and replacement interval. Median and arithmetic mean were used. The results were expressed in graphs and tables. Results: The occupational index experienced a rising trend as it was the highest in 2018 with 66.9% affecting the services of neuropediatrics (88.1) and general pediatrics (78). Hospital stay showed a significant increase in 2018 although it did not exceed 4 days or in the services that treated these patients, which could correspond to difficulties in active case surveillance. The turnover rate and replacement interval were consistent with the occupational index, hospital stay and type of hospital. Conclusions: Changes in hospital indicators related to the efficient use of the bed resource were noticed, being more evident in 2018, a period in which dengue cases were reported in the province.